2022
DOI: 10.3389/fmed.2022.886936
|View full text |Cite
|
Sign up to set email alerts
|

Willingness to Be Vaccinated Against COVID-19 Among People With HIV in the United States: Results From a National Survey

Abstract: BackgroundApproximately 215 million Americans have been fully vaccinated for COVID-19, representing over 65% of the total population. People with HIV (PWH) may be more susceptible to COVID-19 infection or severe disease, elevating the importance of COVID-19 vaccination uptake in the population. We report results from a national survey of PWH to evaluate the likelihood of receiving a COVID-19 vaccine.MethodsWe conducted an online survey of 1,030 PWH living in the United States between December 6, 2020 and Janua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 14 publications
2
14
1
Order By: Relevance
“…Of the respondents, 85.4% were prone to vaccination and it has not been influenced by media. It has been reported that they would be more willing to receive a COVID‐19 vaccine if it was recommended by their doctor (61.5%) or if their doctor mentioned that they had been vaccinated themselves 16 . Our survey timing was vaccination first phase in Spain.…”
Section: Discussionmentioning
confidence: 99%
“…Of the respondents, 85.4% were prone to vaccination and it has not been influenced by media. It has been reported that they would be more willing to receive a COVID‐19 vaccine if it was recommended by their doctor (61.5%) or if their doctor mentioned that they had been vaccinated themselves 16 . Our survey timing was vaccination first phase in Spain.…”
Section: Discussionmentioning
confidence: 99%
“…2,20,21 When COVID-19 vaccines became public, health authorities found public acceptance and dispersion of vaccines were suboptimal due to mistrust and safety and efficacy concerns. 22 For PLWH who had compromised immune systems, concerns about vaccine safety and efficacy were amplified. 7 We conducted this analysis to provide insight on the impact of COVID-19 directly from PLWH based on a sample of 5 Medical Monitoring Project (MMP) sites across 2 project cycle years of data collection, from mid-2020 through mid-2022.…”
Section: Introductionmentioning
confidence: 99%
“…11 In addition, hesitation was found to be associated with medical mistrust, feelings of vaccines being experimental, obtaining information from social media, political conservativeness, and lower education level. 813…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Despite the vaccine effectiveness, the rates of COVID-19 vaccine hesitancy among PLHIV ranges from 16%-91% depending on the study settings and the points of time when the studies were conducted. [8][9][10][11][12][13] The main reasons for vaccine hesitation were concerns about safety, 8-13 efficacy [8][9][10][11][12][13] and the impact of the vaccines on antiretroviral therapy (ART) efficacy. 11 In addition, hesitation was found to be associated with medical mistrust, feelings of vaccines being experimental, obtaining information from social media, political conservativeness, and lower education level.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation